EFFECT OF CONTENT BASED APPROACH OF LANGUAGE TEACHING IN STUDENTS’ PERFORMANCE OF GOVERNMENT COLLEGE KAGORO - Danjuma, Baita Edwards; Bawa, Inuwa Danladi; Bahago, Ishaku; Awulo, Okan Samson (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aimed to assess the effect of Content Based Language Teaching (CBLT) on vocabulary development among Senior Secondary School (SSS) students at Government College Kagoro. Method: A Pre-Test and Post-Test design was adopted, with the population drawn from senior student classes. The data were collected through the results of the Pre-Test and Post-Test administered to both the experimental and control groups.  Results:  The findings indicated that CBLT significantly enhanced vocabulary development, with the experimental group outperforming the control group. CBLT proved effective in improving students' ability to learn and apply new words. Novelty: The novelty of this study lies in its focus on the specific impact of CBLT on vocabulary acquisition at the Senior Secondary School level, highlighting its potential for improving language skills in this educational context.